Pathogenic variability of Colletotrichum sp. from chilli anthracnose and their tolerance to carbendazim: Pathogenic variability of Colletotrichum sp. (Journal of the Bangladesh Agricultural University, 2018)
Twelve isolates of Colletotrichum capsici and Colletotrichum gloeosporides were isolated from anthracnose infected chilli fruits from different areas of Mymensingh. Isolated pure fungal isolates were grouped on the basis of their morphological characters viz. colony color and compactness, size, shape and number of conidia. The white colored isolates were identified as C. capsici and showed faster growth on PDA medium. In contrast, grey colored fungal isolates were identified as C. gloeosporides and comparatively slow growth on PDA medium. All the fungal isolates were pathogenically active and developed typical symptoms on both green and ripe fruits of chilli. The isolates of C. capsici collected from Kalibari showed the highest infection (74.99%) on fruit surface followed by Muktijoddhar bazar (61.83%). Differential tolerance was observed as fungal growth was different against 0.05% and 0.1% carbendazim while 0.2% carbendazim was lethal against all fungal isolates. The results indicate that severity of anthracnose of chilli is different may be due to aggressiveness of fungal and their tolerance against common fungicide like carbendazim.J.Bangladesh Agril. Univ. 16(3): 417–423, December 2018